Identification of Phytophthora citrophthora with Cloned DNA Probes - Goodwin, P. H. (1990)
Two different DNA fragments, one of 2.9 kilobases and the other of 5.1 kilobases, were cloned from Phytophthora citrophthora and showed no homology with DNA from plants and other related fungi. These DNA probes hybridized with DNA from 12 different P. citrophthora isolates obtained from a variety of hosts but did not hybridize with DNA from 6 P. citrophthora isolates obtained from cacao. Southern blot analysis revealed that the probes contained repetitive DNA, and restriction fragment length polymorphisms were identified among several P. citrophthora isolates. Of the isolates tested, two major groups were observed whose genetic similarity correlated with geographical distribution. One of the DNA probes was used to detect P. citrophthora growing from infected citrus roots incubated on semiselective medium. P. citrophthora was not detected by a hybridization assay of total DNA extracted directly from infected roots.